O concerto para viola e orquestra de antônio borges-cunha: Forma e interpretação - Kubala, Ricardo Lobo [UNESP]; De Biaggi, Emerson Luiz (My University, 2013)
This article has as object of study the Concerto for Viola and Orquestra by Antônio Borges-Cunha. We investigated the work by observing its formal structure. This resulted in data which were relevant to the understanding of the work itself and to decisive procedures in its interpretation. These data were then applied to specific issues in the area of performance, by means of a process whereby the sensations of movement and direction were delineated. This investigation discusses interpretation and the queries regarding the paths which performers can choose in their quest for positive results in expressivity. It is a study specifically geared to the area of performance and, in a broader sense, serves composers that are interested in the performer's contribution to the creative process of a work.
The concerto for viola and orchestra by antônio borges-cunha: Form and interpretation
Keywords: Brazilian contemporary music; Music for viola and orchestra; Musical interpretation